The influence of the use of information technology and professionalism on employee performance mediated by work productivity - Dori Mittra Candana; Hapzi Ali; Zefriyeni Zefriyeni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
One of the companies in the Indonesian cement industry is PT Semen Padang (Persero) Tbk. With the entry of new companies, the Indonesian cement industry will improve the quality of its products amidst intense industrial competition. The aim of this research is to discover, analyze and measure the direct impact that employee performance has on the use of information technology, training and productivity. This research method is quantitative using inferential statistics (parametrik). The quantitative research was conducted using the structural equation modeling (SEM) model analysis with a few exogenous and endogenous variables.The data needed for this study are derived from two primary sources: 1) data primer (data primer) and 2) data sekunder (data sekunder). The primary data comes from the questioner's daftar, which is sent to the PT Semen Padang clerk. Semen padang.co.id and the Badan Pusat Statistik (BPS) Sumatera Barat are the sources of the second-hand data.The number of samples that met the research criteria was 296 employees of PT Semen Padang (Persero) Tbk. The results of data processing show that the use of information technology has a positive and significant effect on employee performance, professionalism has a positive and significant effect on employee information performance, the use of technology has a positive and significant effect on work productivity, professionalism has a positive and significant effect on work productivity, productivity has a positive and significant effect on employee performance, the use of technology has a positive and significant effect on employee performance, mediated by work productivity and professionalism has a positive and significant effect on employee performance, mediated by work productivity at PT cement Padang (Persero) Tbk.